Isolation and Molecular Cloning of Carbohydrate Binding Module (CBM40) From Vibrio cholerae Non-O1 Neuraminidase - Nadiawati, Alias (2018)
Carbohydrate binding modules (CBMs) are discrete contiguous amino acid sequence within a carbohydrate-active enzyme which are, non-catalytic modules that primarily exist to target parent enzyme to its substrate for efficient hydrolysis. Although many sialidase proteins have been identified from various pathogenic bacteria, only a few enzymes are commercially available which have been used for chemoenzymatic syntheses and therapeutics application. In order to study family 40 CBM domain, a number of bacteria have been screened including Pseudomonas aeruginosa ATCC 27853, Bacillus cereus ATCC 14579, Staphylococcus aureus ATCC 33862, Salmonella thypii ATCC 14028 and Vibrio cholerae Non-O1. A gene encoding CBM40 domain was screened from all the bacteria strains and subjected to PCR amplification. From all the samples tested, only Vibrio cholerae Non-O1 amplified a PCR product with approximate size of 530 bp. From BLAST sequence analysis, result has shown 99% similarity with the target Vibrio cholerae neuraminidase, NanH (M83562). Next, the confirmed CBM40 gene was further ligated into pGEMT Easy Vector system and transformed into E. coli JM109 host to secure the clone before re-ligated into suitable expression vector.